Au-delà du mur : Israël face à sa frontière - Pierre Renno (EchoGéo)
Built on the opposition between the concepts of border and frontier, this article is aimed at showing that the construction of the separation fence does not signify the emergence of a border. On both sides of the Green Line, Israeli territorial practises are still expressing a frontier logic. In this logic, it’s the settlement of a space by a population ethnically identified with the pioneer group that makes this space a State territory. The existence of an open frontier thus contributes to invert the classical link between population and territoriality. The demos, the people, is not defined territorially as the individuals residing in the State territory; it is rather defined ethnically and it’s its spatial dispersion that builds the State territory.